Allergen immunotherapy for the prevention of allergic disease: protocol for a systematic review. Issue 3 (21st January 2016) - Dhami, Sangeeta; Nurmatov, Ulugbek; Halken, Susanne; Calderón, Moises A.; Muraro, Antonella; Roberts, Graham; Toit, George Du; Kleine‐Tebbe, Jörg; Larenas‐Linnemann, Desiree; Lau, Susanne; Matricardi, Paolo Maria; Pajno, Giovanni; et al.
Abstract: Background: The European Academy of Allergy and Clinical Immunology (EAACI) is in the process of developing the EAACI Guidelines for Allergen Immunotherapy (AIT) for the Prevention of Allergic Disease. We seek to critically assess the effectiveness, cost‐effectiveness, and safety of AIT in the prevention of allergic disease. Methods: We will undertake a systematic review, which will involve searching international biomedical databases for published, in progress and unpublished evidence. Studies will be independently screened against pre‐defined eligibility criteria and critically appraised using established instruments. Data will be descriptively and, if possible and appropriate, quantitatively synthesized. Discussion: The findings from this review will be used to inform the development of recommendations for EAACI's Guidelines on AIT.